A rapid and quantitative safranin‐based fluorescent microscopy method to evaluate cell wall lignification. (18th February 2020) - Baldacci‐Cresp, Fabien; Spriet, Corentin; Twyffels, Laure; Blervacq, Anne‐Sophie; Neutelings, Godfrey; Baucher, Marie; Hawkins, Simon
Summary: One of the main characteristics of plant cells is the presence of the cell wall located outside the plasma membrane. In particular cells, this wall can be reinforced by lignin, a polyphenolic polymer that plays a central role for vascular plants, conferring hydrophobicity to conducting tissues and mechanical support for upright growth. Lignin has been studied extensively by a range of different techniques, including anatomical and morphological analyses using dyes to characterize the polymer localization in situ . With the constant improvement of imaging techniques, it is now possible to revisit old qualitative techniques and adapt them to obtain efficient, highly resolutive, quantitative, fast and safe methodologies. In this study, we revisit and exploit the potential of fluorescent microscopy coupled to safranin‐O staining to develop a quantitative approach for lignin content determination. The developed approach is based on ratiometric emission measurements and the development of an imagej macro. To demonstrate the potential of our methodology compared with other commonly used lignin reagents, we demonstrated the use of safranin‐O staining to evaluate and compare lignin contents in previously characterized Arabidopsis thaliana lignin biosynthesis mutants. In addition, the analysis of lignin content and spatial distribution in the Arabidopsis laccase mutant also provided new biological insights into the effects of laccase gene downregulation in different cell types. Our safranin‐O‐based methodology, also validated for Linum usitatissimum (flax), Zea mays (maize) and Populus tremula x alba (poplar), significantly improves and speeds up anatomical and developmental investigations of lignin, which we hope will contribute to new discoveries in many areas of cell wall plant research. Significance Statement: Lignin has long been the subject of extensive study as it plays a major role in plant growth and defense and is an important factor affecting the quality of plant biomass and plant‐derived products. The development of an easy and quantitative confocal microscopy method to provide detailed spatial information about lignin content at the cell wall level will prove a valuable addition to the toolbox of lignin analytical methods for both fundamental and applied research.